Pemanfaatan Limbah Sampah Plastik Kota Bangkalan sebagai Bahan Baku Genteng dengan Menggunakan Mesin Hotpress - Indriartiningtias, Retno; Ahmad, Sabarudin; Fathkur Rhozi, Arista (Jurnal Pengabdian Masyarakat Charitas, 2024)
Plastic waste is a waste that is difficult to decompose, and plastic waste is a problem that until now has not been resolved by the Indonesian government, especially the local government of Bangkalan Regency. The Bangkalan Environmental Agency (DLH) stated that in 2022, there will be around 100 tons/year of potential waste generated. As a result of the waste generation data, DLH experienced complaints about the increasing use of plastic and was not balanced with plastic waste management. This activity aims to provide alternative utilization of plastic waste in the form of HDPE plastic-based roof tiles using a pneumatic hotpress machine made by students of the Industrial Engineering Manufacturing Laboratory, Trunojoyo University Madura. With this alternative waste utilization opportunity, it is not only one of the solutions to reduce plastic waste, but also can be used as a business opportunity by Bangkalan residents.